Βελτιστοποίηση εκμετάλλευσης μαρμάρου με τη βοήθεια γεωφυσικών ερευνών - Καραΐσκος, Δημήτριος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανικών Μεταλλείων Μεταλλουργών, 2017)
The diploma thesis examines the case of the “Dionyssos” marble open cast quarry, which is located at the Penteli Mountain. The company exploits a white to semi-white marble statigrafically overlying the famous “Pentelikon marble” The “Dionyssos” quarry is in the “Almyropotamos-Attiki” autochthonous unit which is a big unit of formations occurring at the internal zones area in form of tectonic windows that belongs to the huge platform of Gavrovo-Tripolis zone. The marble extracted from the “Dionyssos” quarry is white calcitic and belongs to the so-called “lower marble” horizon. The main tectonic characteristic of the quarry area is the existence of an upfold with a south-western to north-eastern orientation as well as the variety of natural fractures that cut into pieces the marble area, resulting in the low recovery rate of high quality marble blocks. The aim of the diploma thesis is to investigate the possibility of optimizing the exploitation in the marble quarry through the early detection of discontinuities, using non-destructive testing methods, during the cutting process. For this purpose, alternative geophysical methods were applied in situ to both outdoor and underground facilities and ore specifically, the methods applied were: a) ground penetrating radar (GPR), with Mala GPR (250 MHz and 500 MHz) shielded antenna, b) Electrode Method (EDT), Dipole dipole and c) Electromagnetic , with a Gf (CMD-2) conductivity instrument with both coil orientations.. The evaluation of the geophysical methods has revealed that all the methods examined can give reliable results, up to 4 m deep. The most appropriate, however, for such a work seems to be the GPR method, as it can be applied relatively easily, it does not affect the production process, while the images that derive from the processing facilitate the interpretation of the results.